Pupuk Hayati dan Kepadatan Tanaman: Strategi Peningkatan Produktivitas Jagung Manis (Zea mays var. saccharata, Sturt) - Hengky Wattimena; A. Marthin Kalay; Anthony Walsen; Abraham Talahaturuson (AGROLOGIA: Jurnal Ilmu Budidaya Tanaman, 2025)
Increasing sweet corn productivity sustainably can be achieved through environmentally friendly cultivation techniques, including the use of biological fertilizers and plant population regulation. This study aims to evaluate the effects of combining different types of biofertilizers and the number of seeds per planting hole on the growth and yield of sweet corn. The experiment was arranged using a random design of a factorial group with two factors, namely three types of biological fertilizers (Bacillus spp. consortium, Azotobacter chrococcum–Trichoderma harzianum, combination, and Bion Up®) and three levels of seed count (1, 2, and 3 seeds per hole). The results showed a significant interaction between the two factors on several growth and yield parameters, including plant height (35 HST), weight of 100 seeds, weight of fruit without leaves, fresh weight of economy, and biomass. The combination of Bacillus spp. with two seeds per hole yields the highest weight of 100 seeds, while the combination of Bacillus spp. with three seeds per hole yields the highest weight of fruit without loam.